Free search of equivalent sin translation of environmental terms with allowance for the resemantization - N I Zhabo (RUDN Journal of Ecology and Life Safety, 2014)
To find an equivalent in translation considering the process of the replacement of the content of a linguistic sign by a new meaning, specially created to nominate concepts in ecology (process of resemantization) search techniques are considered. We analyze the use of environmental terms of the French language in a figurative sense.